Solving global challenges locally. Collective housing as a catalyst for ecological transition - Andrés Cánovas; Javier De Andrés (Agathón)
Confronted with the evidence of climate change, architecture can – and must – play an important role in minimising the harmful consequences of this phenomenon; in this sense, collective housing (especially public housing) is beginning to take its first steps in redefining a new energy paradigm and strategies aimed at responding to the challenge posed by the ecological transition. Three indispensable requirements are thus identified: energy passivity, the use of local materials, and reuse and regeneration, conceived as complementary tools to activate a thorough transformation of the built environment. This goal also requires the complicity of three key factors (or actors) related to the housing sector: the real estate sector, the legislation, and the users.